THEORETICAL SUBSTANTIATION OF DIRECT TRANSPORT OF BIOLOGICALLY ACTIVE COMPONENTS IN CONDITIONS OF MODELED GASTROINTESTINAL TRACT - A. V. Evteev; N. V. Gorbunova; O. S. Larionova; A. V. Bannikova (Пищевые системы)
In this paper, the results of studies on the release of biological active compounds from their encapsulated forms under conditions of enzymatic hydrolysis in vitro are presented. In the phase of the model «small intestine» swelling of the capsules and their subsequent decay occurs, which allows to speak about the controlled release of encapsulated bioactive components. It was revealed that almost 90 % of the residual quantity of essential ingredients was released from the capsules in the model phase of the artificial «small intestine». At the end of the experiment, the capsules released all the encapsulated biologically active substances, regardless of the content of fish oil and phenolic compounds in them. It was noted that the poly-capsules had the greatest propensity to withstand the aggressive environment of the «model stomach» and concentrate in themselves the maximum amount of biologically active substances. Mathematical modeling confirms the direct transport of biologically active compounds and the role of the swelling of capsules in the release of biologically active compounds. two mathematical models describing the classical theory of diffusion from capsules and incorporating the material relaxation coefficient demonstrate a combination of empirical and theoretical approaches in controlling the properties of encapsulated biologically active substances. the obtained data are promising in the field of development of improved and functional food products, as well as the dry ingredients and concentrates